Actinomadurone, a polycyclic tetrahydroxanthone from Actinomadura sp. BCC 35430. Issue 33 (16th August 2017) - Bunyapaiboonsri, Taridaporn; Yoiprommarat, Seangaroon; Suriyachadkun, Chanwit; Supothina, Sumalee; Chanthaket, Rungtiwa; Chutrakul, Chanikul; Vichai, Vanicha
Graphical abstract: Highlights: A polycyclic tetrahydroxanthone, actinomadurone, was isolated from the actinomycete Actinomadura sp. BCC 35430. Actinomadurone possess angular hexacyclic aromatic framework with an additional methylenedioxy bridge. Actinomadurone showed antifungal and cytotoxic activities. Abstract: A polycyclic tetrahydroxanthone, actinomadurone, was isolated from the actinomycete Actinomadura sp. BCC 35430. Its structure was elucidated by extensive spectroscopic analyses. Actinomadurone showed antifungal activities against Curvularia lunata, Alternaria brassicicola, Colletotrichum capsici, and Colletotrichum gloeosporioides ; and displayed cytotoxic activity against Vero cell lines.